2018
DOI: 10.15294/higeia.v2i2.21291
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi Kebijakan Permenkes Nomor 67 Tahun 2016 tentang Penanggulangan Tuberkulosis

Abstract: ABSTRAK TB merupakan penyakit menular yang masih menjadi masalah kesehatan masyarakat dan salah satu penyebab kematian, sehingga perlu dilaksanakan program penanggulangan TB secara berkesinambungan. Tujuan penelitian adalah menganalisis implementasi kebijakan tentang penanggulangan TB di Kota Tegal. Jenis penelitian ini merupakan penelitian kualitatif dengan teknik pengambilan informan secara purposive sampling. Informan utama yaitu pengelola program TB di fasyankes dan petugas analis di fasyankes. Uji v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…The study results in Tegal City found that TB cases with contact investigations were never performed because of the large number of TB officers working at the Puskesmas [16]. Moreover, improving the implementation of ACF TB through contact finding by TB cadres needs substantial support from health workers in Puskesmas.…”
Section: Discussionmentioning
confidence: 96%
“…The study results in Tegal City found that TB cases with contact investigations were never performed because of the large number of TB officers working at the Puskesmas [16]. Moreover, improving the implementation of ACF TB through contact finding by TB cadres needs substantial support from health workers in Puskesmas.…”
Section: Discussionmentioning
confidence: 96%
“…Whereas in the midst of limited human resources or TB program officers who are only one person in the health center, the presence of cadres provides the extraordinary potential for increasing the quantity and quality of contact investigations. Faradis and Indarjo (2018) in the results of their research in Tegal City stated that coordination between government agencies and private agencies and community organizations is needed to support the achievement of the goals and objectives of the TB mitigation program.…”
Section: Resourcesmentioning
confidence: 99%
“…Sebuah hasil penelitian sebelumnya menyimpulkan kebijakan di kota Tegal untuk menanggulangi TB belum terlaksana dengan optimal. Terdapat dua determinan yang baru terimplementasi dengan baik dari empat determinan penanggulangan TB yaitu sumber daya kebijakan dan dukungan masyarakat dalam penanggulangan TB (Faradis & Indarjo, 2018). Memperimbangkan kajian teori dan studi lapangan tersebut, peneliti tertarik untuk melakukan asuhan keperawatan secara koprehensif.…”
Section: Pendahuluanunclassified